Lymphocytic gastritis–prospective study of its relationship with varioliform gastritis. Issue 3 (March 1990) - Haot, J; Jouret, A; Willette, M; Gossuin, A; Mainguet, P
Abstract : Lymphocytic gastritis is a new histopathological entity characterised by a dense lymphocytic infiltration of surface and pit gastric epithelium. Previous retrospective work has suggested that lymphocytic gastritis is related to an endoscopic form of gastropathy comprising enlarged folds, nodules and erosions, commonly denoted as varioliform gastritis. In the present prospective study, the relationship is clearly shown; nearly 82% (54/66) of the varioliform gastritis observed in four different endoscopy units correspond histologically to lymphocytic gastritis. The correlation is even better if cases showing strictly antral localisation are excluded (53/55) - that is, more than 96%. The histological concept of lymphocytic gastritis seems, however, to extend beyond varioliform gastritis as of 67 cases of lymphocytic gastritis diagnosed during the period under study, one third had no particular endoscopic expression.